India’s Role in Afghan Peace Process - Dr. Ghulam Mustafa; Aamir Junaid; Rana Basam Khan; Imran Wakil (Journal of Political Studies, 2020)
The disastrous event of 9/11 changed the Political and Security dynamics of the world. The event of 9/11 provided a chance for India to enter into Afghanistan. Afghanistan attracts the world powers due to its strategic importance. Afghanistan is a gateway to the energy rich Central Asian Republics. India’s involvement in Afghanistan is quite realistic. India had never established cordial relations with the Taliban regime in Afghanistan. The event of 9/11 gave India a chance to establish cordial relations with the Afghan political government. India participated in the Bonn Conference and announced its support for the people of Afghanistan in the reconstruction of the country. India enjoyed its best relations with the governments of Hamid Karzai and Ashraf Ghani in Kabul. India enhanced its ties with Iran to secure its interest in Afghanistan and to counter Pakistan. India and Iran have some common interests in Afghanistan. New Delhi has invested a big amount in various sectors in Afghanistan to enhance its influence in Afghan society. India has worked hard to facilitate Afghan Nationals to boost its soft power. India now influences the internal politics of Afghanistan. The world considers India a major market in South Asia. India’s presence in Afghanistan has always been a source of worry for Pakistan. Pakistan considers India’s presence in Afghanistan a threat to its National Security. Pakistan thinks India should work for the betterment of Afghan people but she should avoid using Afghan soil against Pakistan. Pakistan has already suffered a lot due to the disturbance in Afghanistan. Peaceful Afghanistan is in the favor of South Asia and for the Global Powers. This paper focuses on the Indian presence in Afghanistan and India’s role to bring peace in Afghanistan.